5-Hydroxymethylcytosine in cord blood and associations of DNA methylation with sex in newborns. (6th October 2019) - Solomon, Olivia; Macisaac, Julia L; Tindula, Gwen; Kobor, Michael S; Eskenazi, Brenda; Holland, Nina
Abstract: DNA methylation has been widely studied for associations with exposures and health outcomes. Both 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC) are epigenetic marks that may function differently to impact gene expression; however, the most commonly used technology to assess methylation for population studies in blood use are the Illumina 450K and EPIC BeadChips, for which the traditional bisulfite conversion does not differentiate 5mC and 5hmC marks. We used a modified protocol originally developed by Stewart et al. to analyse oxidative bisulfite-converted and conventional bisulfite-converted DNA for the same subject in parallel by the EPIC chip, allowing us to isolate the two measures. We measured 5mC and 5hmC in cord blood of 41 newborn participants of the Center for Health Assessment of Mothers and Children of Salinas (CHAMACOS) birth cohort and investigated differential methylation of 5mC + 5hmC, isolated 5mC and isolated 5hmC with sex at birth as an example of a biological variable previously associated with DNA methylation. Results showed low levels of 5hmC throughout the epigenome in the cord blood samples in comparison to 5mC. The concordance of autosomal hits between 5mC + 5hmC and exclusive 5mC analyses were low (25%); however, overlap was larger with increased effect size difference. There were 43 autosomal cytosine nucleotide followed by a guanine nucleotide (CpG) sites where 5hmC was associated with sex, 21 of which were unique to 5hmC after adjustment for cell composition. 5hmC only accounts for a small portion of overall methylation in cord blood; however, it has the potential to impact interpretation of combined 5hmC + 5mC studies in cord blood, especially given that effect sizes of differential methylation analyses are often small. Several significant CpG sites were unique to 5hmC, suggesting some functions distinct from 5mC. More studies of genome-wide 5hmC in children are warranted.